"Be Careful What You Wish for": U.S. Government Enforcement of Merger Consent Decrees. (June 2013) - Gelfand, David; Ewing, Elaine
The U.S. Federal Trade Commission and Department of Justice Antitrust Division have a number of formal and informal tools at their disposal to enforce merger consent decrees. This article reviews these tools, the frequency with which they are used, and the circumstances under which they are used, with a particular focus on instances in which the agencies have taken formal enforcement action. Because these obligations should be considered carefully during the negotiation process, the article concludes by offering practical advice for antitrust practitioners negotiating consent decrees.